Hubungan Employability Skills dengan Kesiapan Kerja Siswa di SMK N 1 Sawit - Arif Budi Anto; Ngatou Rohman; Towip Towip (Fakultas Keguruan dan Ilmu Pendidikan Universitas Sebelas Maret Surakarta, 2024)
This study aims to (1) determine the relationship between employability skills and work readiness of SMK N 1 Sawit students. The research method used is quantitative descriptive which is described from the data results. The sampling technique in this research was simple random sampling or random sampling with a total of 140 class Data collection was carried out using questionnaires from class XII students who concentrated in the mechanical field. The validity test technique was carried out by comparing the calculated r value with the table r value and a reliability test using the Cronbach's Alpha formula > 0.6 using a sample of 30 students and obtained results for employability skills of 0.957 and work readiness of 0.800. The analysis prerequisite tests in this research consist of normality tests and linearity tests which aim to determine the normality of the data and the suitability of data that has been filled in by 140 students who concentrate on machines and processed using SPSS version 26.0. So that normal and linear data results are obtained. Hypothesis testing in this study uses the Pearson correlation test to determine the relationship between two variables. The research results are as follows, there is a positive relationship between the employability skills variable and students' work readiness at SMK N 1 Sawit where employability skills have a relationship with work readiness. The value of the effective contribution was 70.8%, while the remaining 29.2% was influenced by other factors, both internal and external to each individual.